Characterisation of novel T cell specific IL-4 receptor-alpha knockout mice : investigating the role of T cell responses to IL-4 in Leishmania major and Nippostrongylus brasilliensis infections - Hoving, Claire (Department of Medicine, 2014)
Includes bibliographical references (leaves 76-86).